HUBUNGAN ANTARA PERILAKU DENGAN GANGGUAN FUNGSI PARU PADA PEKERJA UNIT II PENGOLAHAN NPK DI INDUSTRI PT. PETROKIMIA GRESIKDust generated from processes of Nitrogen Phosphate Potassium (NPK) fertilizer production, can disperse in the workplace and harm to - Prehatin Trirahayu Ningrum (Fakultas Kesehatan Masyarakat, Universitas Jember, 2012)
Dust generated from processes of Nitrogen Phosphate Potassium (NPK) fertilizer production, can disperse in the workplace and harm to the workers. Generally, organic and inorganic dust exposure will cause obstruction of respiratory tract and indicated by decreasing of %FEV1/%FVC level. Workers of NPK production section in PT. Petrokimia Gresik have high risk from dust deposition on their respiratory tract. This research purpose to analize the assocation between behavior with lung function disorder on workers at Unit II NPK production section in industry PT. Petrokimia Gresik, in Gresik Regency. This research was an observational research with a cross cectional design and 30 samples were taken. Sampling was carried out by using a purposive sampling technique. Data were analyzed by chi-square and multivariate by regresi logistic technique. The result of the research showed that factors which were related to the lung function disorder were exposure the habit of using personal protective device (p=0,023). For factors smoking habits, continuity of the use of masks and exercise habits the analysis can not be done because of the constant variables. It can be concluded that there were relationship between habit of using personal protective devices of workers with lung function disorder. Keyword : Lung Function Disorder, Workers, NPK Production